The Development of Desirable Characteristics on Public Mind for Kindergarteners under the Office of Mahasarakham Primary Education Service Area 1 - Duangta, Malaithong; Promta, U-rasa; Phoojomjit, Pongphop (Journal for Developing the Social and Community, 2021)
The purposes of this research were to study the current state and develop the desirable characteristics on public mind for kindergarteners under the Office of Mahasarakham Primary Education Service Area 1. The research procedures were divided into two phrases. The first stage was to study the current state of the desirable characteristics on public mind for kindergarteners, with 229 samples. The research instrument was a questionnaire. The second stage was the studying of the development of the desirable characteristics on public mind for kindergarteners, with 9 experts by using the formal interview . The results found that: The current state of the desirable characteristics on public mind for kindergarteners in overall was moderate by raking from maximum to minimum average following 1) supporting 2) cooperation 3) common interest and 4) sharing respectively. The development of the desirable characteristics on public mind for kindergarteners under the Office of Mahasarakham Primary Education Service Area 1 comprised of 1) activities supported the development of kindergartener’s public mind 2) curriculum for development of kindergartener’s public mind or learning sets and 3) the good model of being public mind from the administrators, teachers and parents.